2021
DOI: 10.1002/ecs2.3689
|View full text |Cite
|
Sign up to set email alerts
|

Integrating telemetry data at several scales with spatial capture–recapture to improve density estimates

Abstract: Accurate population estimates are essential for monitoring and managing wildlife populations. Mark-recapture sampling methods have regularly been used to estimate population parameters for rare and cryptic species, including the federally listed Mojave desert tortoise (Gopherus agassizii); however, the methods employed are often plagued by violations of statistical assumptions, which have the potential to bias density estimates. By incorporating spatial information into conventional density estimation models, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
(147 reference statements)
0
5
0
Order By: Relevance
“…More common in SCR studies is that the recapture rate is lower, for example, L opez-Bao et al ( 2018) detected 65 individual wolves from scat surveys, but the recapture rate was only 1.46. Similarly, Mitchell et al (2021) found 143 individual tortoises in their study but had very few recaptures. However, both studies collected concurrent telemetry data that were used to improve the fit of standard SCR models and, with the models presented here, these types of studies could be expanded to examine resource use and the potential effects on the demographic rates.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…More common in SCR studies is that the recapture rate is lower, for example, L opez-Bao et al ( 2018) detected 65 individual wolves from scat surveys, but the recapture rate was only 1.46. Similarly, Mitchell et al (2021) found 143 individual tortoises in their study but had very few recaptures. However, both studies collected concurrent telemetry data that were used to improve the fit of standard SCR models and, with the models presented here, these types of studies could be expanded to examine resource use and the potential effects on the demographic rates.…”
Section: Discussionmentioning
confidence: 84%
“…Taking advantage of advancements in bio‐logging data, we can fully capitalize on integrated SCR movement models and provide a means for a better understanding of the ecological processes driving movement and demography. However, this integration presents some challenges, including spatial or temporal mismatch between the SCR data and the location data (Mitchell et al, 2021). In cases of spatial mismatch, auxiliary location data could be used as the basis for an informative prior on the movement model parameters (e.g., σ 2 , γ) or included in the movement model likelihood, but they should not be used to inform the detection parameters (e.g., σdet2$$ {\upsigma}_{\mathrm{det}}^2 $$, λ 0 ) or population size ( N ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified environmental features associated with the presence of tortoises throughout their geographic range (Nussear et al, 2009), but less effort has been directed toward identifying environmental features that explain variation in density. Although other studies have provided local estimates of density (e.g., Berry et al, 2020; Mitchell et al, 2021), data limitations and computational hurdles have made it challenging to generate rigorous estimates that are comparable across the species' range. By leveraging data from the range‐wide survey effort led by USFWS and using recent modeling and software advancements, we were able to estimate local densities and regional trends across much of the range of the Mojave desert tortoise.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of density across the survey region were low (<10 tortoises/km 2 ) compared with historical estimates of some local populations that ranged as high as 50–100 adult tortoises/km 2 (Berry & Medica, 1995; Berry et al, 2020). These examples are exceptional and not representative of tortoise populations range‐wide, however, as they are likely biased high due to violations of analytical assumptions (Mitchell et al, 2021; USFWS, 2011). On average, our density estimates were also lower than many contemporary estimates (e.g., Mitchell et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation